Plant Growth Response of Pinus patula and P. maximinoi Seedlings at Nursery to Three Types of Ectomycorrhizal Inocula - Manuel F. Restrepo-Llano; Nelson W. Osorio-Vega; Juan D. León-Peláez (Applied and Environmental Soil Science)
The objective of this study was to assess the response in seedling growth, root colonization, and P content of seedlings of Pinus maximinoi and P. patula to the inoculation with three types of ectomycorrhizal inocula with three doses (17.5, 35, and 70 kg·m−3) in nursery. The first inoculum was soil from a Pinus plantations that contained three ectomycorrhizal fungi (Amanita muscaria, Amanita sp., and Suillus luteus); the second was a crude inoculum composed by root fragments of Pinus seedlings colonized by S. luteus suspended in a sterile matrix soil-sand; the third inoculum was a mixture of two ectomycorrhizal fungi A. muscaria and S. luteus produced under in vitro conditions in the potato-dextrose-agar medium. The results showed that the inoculum produced in vitro was most effective to promote plant growth and ectomycorrhizal colonization of roots in both plant species. Also, the effects on seedlings were significantly higher with the increase of the doses. In P. patula there were not significant effects on foliar P content with type and dose of inocula, whereas in P. maximinoi there were interactive effects of both factors. In this case, better results were obtained with the inoculum produced under in vitro conditions and with the highest dose.